Elderly primigravida and a comparative analysis of their pregnancy outcome with younger primigravida - Pegu, Bhabani; Gaur, Bhanu Pratap Singh (International Journal of Research in Medical Sciences, 2018)
Background: Though pregnancy and child birth is a normal physiological process but a woman with advanced age is a risk factor for adverse pregnancy outcome. This study was conducted to find out the proportion of elderly primigravida and to compare their pregnancy outcome with that in younger primigravida of aged 20-25yrs. Methods: A retrospective study was carried out over a period of two years in a tertiary care hospital of Meghalaya. Secondary data on obstetrics outcome of 54 elderly primigravida aged ≥35 years (study group) was compared to 120 younger primigravida (control group) of aged 20-25 years, delivered during the period of study. The chi square test and Fisher’s exact test were used for statistical analysis and p value of <0.05 was taken as level of significance. Results: During two years of study period, 2048 patients had delivered, out of which 411 (20.1%) were primigravida, 54 (2.6%) were elderly primigravida, 120 (5.9%) were in the younger age groups and 66 (3.2%) were teenage pregnancy. Pregnancy induced hypertension (PIH) with preeclampsia 12 (22.2%), preterm labour 2 (3.7%), instrumental delivery 6 (11.1%), caesarean section 32 (59.3%) were found significantly higher in study group. Conclusions: In our study, the prevalence of elderly primigravida was 2.6% and they had high rates of complications during antenatal period and course of labour than younger primigravida.